2007
DOI: 10.1002/ajim.20472
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary breaks and stretching exercises for data entry operators: A follow‐up field study

Abstract: These results provide further converging evidence that supplementary breaks reliably minimize discomfort and eyestrain without impairing productivity. Low compliance in performing stretches prevented valid assessment of stretching effects. Further research on stretching exercises and exercise compliance is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 27 publications
7
103
3
8
Order By: Relevance
“…These results were in line with previous findings showing a beneficial and preventive effect of rest breaks on occupational injuries (3, 9, 13) and health (10)(11)(12). However, only very few studies have explored rest break length effects on safety and performance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results were in line with previous findings showing a beneficial and preventive effect of rest breaks on occupational injuries (3, 9, 13) and health (10)(11)(12). However, only very few studies have explored rest break length effects on safety and performance.…”
Section: Discussionsupporting
confidence: 82%
“…Only a few studies have explored the effect of rest breaks on temporal trends in occupational injuries, and showed that, after a rest break, the injury risk almost returned to the baseline risk level measured at the start of work (9). Additionally, findings in office settings support the beneficial effect of additional short breaks on health and productivity (10)(11)(12). However, the preventive effect of rest breaks might differ depending on the work environment (13).…”
Section: Includes a Minimummentioning
confidence: 95%
“…Among the 11 medium-and high-quality studies, we found four types of interventions: (i) Four studies examined interventions targeting the work-rest cycle through five-minute supplementary pauses (53,55) Additional records were identified in the bibliographies of primary studies or reviews. Expert consulting did not yield new records.…”
Section: Description Of Interventionsmentioning
confidence: 99%
“…Healthy working behavior is needed to guard the well-being of knowledge workers and reduce health risks. Taking regular short breaks, for instance, can help reduce the risks of repetitive strain injury [15] as well as sedentary behavior [16]. Various studies have investigated the advantages of taking short breaks (also called microbreaks) for computer workers, and characteristics of these breaks (see e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%